Highly active photocatalytic paint for NOx abatement under real-outdoor conditions - Joana Ângelo (2014)
In this work the photocatalytic activity of paints incorporating commercial titanium dioxide for outdoor nitrogen oxide (NO) photoabatement is assessed. The paint acts as a 3D support of the photocatalyst and thus allows a larger amount of TiO2 nanoparticles to absorb light and to contact with pollutants, when compared with a 2D photocatalytic surface. NO conversion and selectivity towards nitrites and nitrates were determined according to the standard ISO 22197-1:2007 (E). Paint coatings were formulated and tested under laboratory and outdoor conditions. The best paint formulation incorporates CristalACTiVTM PC500 photocatalyst from Cristal and calcium carbonate extender, presenting a NO conversion of ca. 70% and a selectivity of ca. 40% under laboratory conditions. The same photocatalyst but characterized in the form of an optically thick film of compressed powder presented ca. 95% and 45% of conversion and selectivity, respectively. Under the real-outdoor conditions, the best performing paint showed a NO conversion of about 95%.